Physiological dosages of estradiol and diarylpropionitrile decrease depressive behavior and increase tryptophan hydroxylase expression in the dorsal raphe nucleus of rats subjected to the forced swim test. Issue 2 (16th January 2019) - Yang, Fuzhong; Cheung, Amy; Tao, Jing; Zhao, Nan; Wan, Wenbin; Sheng, Jianhua
Abstract : The dorsal raphe nucleus (DR) is a crucial source of serotonin (5-HT) neurons involved in the regulation of stress-induced depression. Estrogen receptors have been identified in the DR, yet the role of estrogen in modulating this adaptive response is incompletely understood. The current study investigated the effects of different dosages of estradiol (E2, 10 and 50 μg/rat/day for 11 consecutive days) and selective estrogen receptor modulators: Diarylpropionitrile (DPN, 10 μg/rat/day for 11 consecutive days) and propyl pyrazole triol (PPT, 10 μg/rat/day for 11 consecutive days) on behavior and the expression of tryptophan hydroxylase (TPH) and glucocorticoid receptor in the DR of ovariectomized rats subjected to the forced swim test (FST). 10 μg E2 and DPN, an estrogen receptor β agonist, increased swimming and decreased immobility in the FST, while 50 μg E2 and PPT, an estrogen receptor α agonist, failed to influence the behavior of the rats in the FST. Similarly, 10 μg E2 and DPN increased TPH protein expression in the DR, while 50 μg E2 and PPT did not. Both 10 μg E2 and 50 μg E2 increased glucocorticoid receptor protein expression in the DR. Interestingly, 50 μg E2 led to a greater increase in plasma corticosterone levels compared with 10 μg E2 . These observations suggest that a physiological dosage of E2 reduces depressive behavior and enhances TPH expression. High dosage of E2 lacks antidepressant activity in part due to heightened effects on corticosterone levels, which may conversely decrease TPH expression in the DR.